BMEiCON 2019 Programs and Abstracts - Sumet Umchid; Pateemoh Samae; Suprakorn Sangkarak; Thidarat Wangkram; Hannah Riedle; Peter Wittmann; Jrg Franke; Karl Rssler; Jaroonrut Prinyakupt; Kittipan Roongprasert; Thanakorn Yootho; Teerasak Wongkedsada; et al. (My University, 2019)
The transportation of blood is one of the most important issues in the hospital and healthcare sector since the blood bags have to be kept within a certain range of the temperatures for the entire travel time in order to maintain blood quality during transportation.Therefore, the objective of this work is to design, develop and construct a temperature controlled blood 1570592384
Keywords: Blood donation and transfusion practices